Les enjeux éducatifs du jouet fabriqué par l’enfant dans la Russie des années 1910-1920 - Cécile Pichon-Bonin (Strenae)
This article examines how toys made by children were thought of in an educational context from pre-revolutionary Russia and the early years of Soviet times until the end of the first Five-Year Plan in 1932. The study of texts allows us to see how the actors of the worlds of art and education interpreted the choice of materials, the manufacture (taken both as a type of activity and as a manufacturing process) and the shapes of toys (which refer to the subject represented by a toy and in the style of the representation). The aim here is to identify the main questions running through the debates of the time in order to lay the foundations for the exploration of the educational functions attributed to these toys. We successively examine the evolution of the status of the toy made by the child, considered as an object of study and educational material, the manufacture understood as an educational activity, and finally the articulation between practical, educational and ideological considerations through waste materials.